Advertisement call of Dendropsophus microps (Anura: Hylidae) from two populations from southeastern Brazil - Forti,Lucas Rodriguez (2015)
In anurans, acoustic communication is a major mechanism of pre-zygotic isolation, since it carries information about species recognition. Detailed descriptions of the acoustic properties of anuran advertisement calls provide important data to taxonomist and to the understanding of the evolution of the group. Herein we re-describe the advertisement call of the hylid frog Dendropsophus microps (Peters, 1872) after analyzing a larger sample than that of previous descriptions. We also compare the acoustic properties of the call in two populations and discuss the effect of the presence of the sister species, Dendropsophus giesleri (Mertens, 1950), a potential competitor, in one of the populations. Additionally, we provide information on calling sites and size of males. Males of D. microps emit two types of calls, which differ mainly in pulse repetition rate. Type "A" call has a mean frequency band varying from 4574 to 5452 Hz, (mean dominant frequency = 4972 Hz). Type "B" call has a mean frequency band varying from 4488 to 5417 Hz (mean dominant frequency = 4913 Hz). The calls of D. microps and D. giesleri are the only in the D. parviceps species group that have harmonic structure. The spectral properties of the call showed low intra-individual variation, being considered static, while the temporal properties were highly variable. Compared with males from the Boracéia population, males from the Ribeirão Grande population called from lower perches, and their calls had slightly lower frequency bands and significantly higher pulse rates in their type "B" calls. Inter-populational differences in acoustic properties, body size and use of calling sites could be related to selective forces associated with the presence of the sister species, a potential competitor for the population from Ribeirão Grande.